PENGEMBANGAN MEDIA PEMBELAJARAN POWER POINT DENGAN ISPRING SUITE 9 PADA MATERI LARUTAN PENYANGGA DI SMAN 8 KOTA BENGKULU - Yornia Sianturi; Sura Menda Ginting; Hermansyah Amir (University of Bengkulu, 2025)
This study aims to test the feasibility of the developed learning media and determine student responses using the ADDIE development model. The data collection instruments used were in the form of interviews with chemistry teachers, validation sheets and student response questionnaires. The research was conducted at SMA Negeri 08 Bengkulu City to 30 students of class XI IPA 4. From the research results obtained, the feasibility level of Learning Media in the media aspect is 95.32% while the material aspect is 82.5%. The average percentage of the feasibility level of the Learning Media developed is 89.25%. Based on the results of validation by the Learning Media validator, the developed media is very valid, and based on the results of product trials, the student responses get a percentage of 88.85% which is in the very good category. The results of this study indicate that the Power Point Learning Media with Ispring Suite 9 on the buffer solution material that has been developed is very feasible to use and feasible to be applied to the learning process Keywords: Research and Development; Learning Media; Power Point; Ispring Suite 9; buffer solution